High‐performance work systems as a remedy for growing pains: evidence from South Korean organizations. (1st April 2018) - Kim, Yoon‐Ho; Kim, Youngsang; Kim, Andrea; Han, Kyongji; Lepak, David P
Abstract : Drawing on literatures from a contingency perspective of strategic human resource management and a dynamic resource‐based view, this study examines dynamic patterns of investment in high‐performance work systems (HPWS) to support labor productivity of growing organizations. We analyzed a four‐wave panel dataset from 267 establishments in South Korea and found that higher usage of HPWS at a prior point in time and increasing usage of HPWS over time led to consistently improved labor productivity when the employment size of establishments continued to grow. Our theory and findings provide new insight into the dynamic fit between HPWS and organizational performance over time in growing organizations. Key points: HPWS can benefit the labor productivity of organizations constantly increasing their employment size. Constantly growing organizations can improve their labor productivity by increasing usage of HPWS over time. An HPWS is an effective internal structure to address the growing pains of organizations and realize productive growth.